Enhancing Women’s Well-Being: The Role of Psychological Capital and Perceived Gender Equity, With Social Support as a Moderator and Commitment as a Mediator - Chawla, Sonam; Sharma, Radha R. (Frontiers in Psychology, 2019)
The study is aimed at determining the role of psychological capital and perceived gender equity on employee well-being, particularly women, and assessing if commitment mediates and social support moderates the relationship between psychological capital, perceived gender equity and well-being. Personal survey method was employed for data collection using standardized measures from a representative sample of 433 managers (201 women and 233 men) from private sector companies in India. The findings revealed that perceived gender equity at the workplace positively impacts employee well-being for both men and women, with a greater impact on well-being of women. Besides, facilitating employee well-being, organisations can leverage the mediation relationship of commitment of employees and psychological capital, through training interventions; and can promote perceived gender equity through appropriate policies and practices. It bridges the knowledge gap for developing and utilising psychological capital to enhance employee well-being especially of women, who are under pressure due to their demanding multiple roles at work and home.